Historic and Prehistoric Epidemics: An Overview of Sources Available for the Study of Ancient Pathogens - Antoinette C. van der Kuyl (MDPI AG, 2022)
Since life on earth developed, parasitic microbes have thrived. Increases in host numbers, or the conquest of a new species, provide an opportunity for such a pathogen to enjoy, before host defense systems kick in, a similar upsurge in reproduction. Outbreaks, caused by "endemic" pathogens, and epidemics, caused by "novel" pathogens, have thus been creating chaos and destruction since prehistorical times. To study such (pre)historic epidemics, recent advances in the ancient DNA field, applied to both archeological and historical remains, have helped tremendously to elucidate the evolutionary trajectory of pathogens. These studies have offered new and unexpected insights into the evolution of, for instance, smallpox virus, hepatitis B virus, and the plague-causing bacterium Yersinia pestis. Furthermore, burial patterns and historical publications can help in tracking down ancient pathogens. Another source of information is our genome, where selective sweeps in immune-related genes relate to past pathogen attacks, while multiple viruses have left their genomes behind for us to study. This review will discuss the sources available to investigate (pre)historic diseases, as molecular knowledge of historic and prehistoric pathogens may help us understand the past and the present, and prepare us for future epidemics.